Modular Synthesis of N-Vinyl Benzotriazoles - Singh, Govindra (Org Lett, 2013)
[Image: see text] A modular approach to N1-vinyl benzotriazoles by azide–aryne cycloadditions and Julia–Kocienski reactions is described. Reactions of azidomethyl phenyl-1H-tetrazol-5-yl (PT) sulfide with arynes gave methyl(PT-sulfanyl)-substituted benzotriazoles in 68–89% yields. Oxidation of the sulfides to the sulfones gave the benzotriazole-substituted Julia–Kocienski reagents. Olefination reactions of aldehydes and a ketone with reagents derived from benzyne, 2,3-naphthyne, and 4,5-dimethoxybenzyne precursors proceeded to give various N1-vinyl benzotriazole derivatives. Olefination stereoselectivities are tunable for electron-rich aldehydes, but not for electron-deficient aldehydes and alkanals, where they proceed with good to excellent Z-stereoselectivity.